We're asked to find the derivative

#d/(dx) [(-x^2 + 5)/((x^2 + 5)^2)]#

Use the **quotient rule**, which states

#d/(dx) [u/v] = (v(du)/(dx) - u(dv)/(dx))/(v^2)#

where

#u = -x^2 + 5#

#v = (x^2 + 5)^2#:

#= ((x^2+5)^2d/(dx)[-x^2+5] - (-x^2+5)d/(dx)[(x^2+5)^2])/(((x^2+5)^2)^2)#

Using **power rule** on first term:

#= ((x^2+5)^2(-2x) - (-x^2+5)d/(dx)[(x^2+5)^2])/((x^2+5)^4)#

Use the **chain rule** to differentiate the second term, which in this case is

#d/(dx) [(x^2+5)^2] = d/(du)[u^2] (du)/(dx)#

where

#u = x^2+5#

#d/(du) [u^2] = 2u# (from power rule):

#= ((x^2+5)^2(-2x) - (-x^2+5)(2(x^2+5))d/(dx) [x^2+5])/((x^2+5)^4)#

#= ((x^2+5)^2(-2x) - (-x^2+5)(2x^2+10)(2x))/((x^2+5)^4)#

We can simplify this further if we wanted to:

#= ((x^2+5)^2(-2x) - (-2)(x^2-5)(x^2+5)(2x))/((x^2+5)^4)#

Divide both sides by #x^2+5#:

#= ((x^2+5)(-2x) - (-2)(x^2-5)(2x))/((x^2+5)^3)#

#= (-2x^3 - 10x - (-2)(x^2-5)(2x))/((x^2+5)^3)#

#= (-2x^3 - 10x - (20x - 4x^3))/((x^2+5)^3)#

#= (2x^3 - 30x)/((x^2+5)^3)#

#= color(blue)((2x(x^2-15))/((x^2+5)^3)#